Immune activation and HIV-specific CD8+ T cells in cerebrospinal fluid of HIV controllers and noncontrollers - Ganesh, A; Lemongello, D; Lee, E; Peterson, J; McLaughlin, B; Ferre, A; Gillespie, G; Fuchs, D; Deeks, S; Hunt, P; Price, R; Spudich, S; et al. (Mary Ann Liebert, 2016)
The central nervous system (CNS) is an important target of HIV, and cerebrospinal fluid (CSF) can provide a window into host–virus interactions within the CNS. The goal of this study was to determine whether HIV-specific CD8+ T cells are present in CSF of HIV controllers (HC), who maintain low to undetectable plasma viremia without antiretroviral therapy (ART). CSF and blood were sampled from 11 HC, defined based on plasma viral load (VL) consistently below 2,000 copies/ml without ART. These included nine elite controllers (EC, plasma VL <40 copies/ml) and two viremic controllers (VC, VL 40–2,000 copies/ml). All controllers had CSF VL <40 copies/ml. Three comparison groups were also sampled: six HIV noncontrollers (NC, VL >10,000 copies/ml, no ART); seven individuals with viremia suppressed due to ART (Tx, VL <40 copies/ml); and nine HIV-negative controls. CD4+ and CD8+ T cells in CSF and blood were analyzed by flow cytometry to assess expression of CCR5, activation markers CD38 and HLA-DR, and memory/effector markers CD45RA and CCR7. HIV-specific CD8+ T cells were quantified by major histocompatibility complex class I multimer staining. HIV-specific CD8+ T cells were detected ex vivo at similar frequencies in CSF of HC and noncontrollers; the highest frequencies were in individuals with CD4 counts below 500 cells/μl. The majority of HIV-specific CD8+ T cells in CSF were effector memory cells expressing CCR5. Detection of these cells in CSF suggests active surveillance of the CNS compartment by HIV-specific T cells, including in individuals with long-term control of HIV infection in the absence of therapy.